Don’t Get Me Wrong: ERP Evidence from Cueing Communicative Intentions - Regel, Stefanie; Gunter, Thomas C. (Frontiers in Psychology, 2017)
How to make sure that one’s utterances are understood as intended when not facing each other? In order to convey communicative intentions, in digital communication emoticons and pragmatic cues are frequently used. Such cueing becomes even more crucial for implied interpretations (e.g., irony) that cannot be understood literally, but require extra information. Sentences, such as ‘That’s fantastic,’ may achieve either a literal or ironic meaning depending on the contextual constraints. In two experiments using event-related brain potentials (ERPs), we examined the effects of cueing communicative intentions (i.e., by means of quotation marks) on ironic and literal language comprehension. An impact of cueing on language processing was seen as early as 200 ms post-stimulus onset by the emergence of a P300 preceding a sustained positivity for cued irony relative to literal language, while for uncued irony a P200-P600 pattern was obtained. In presence of additional information for ironic intentions, pragmatic reanalysis allowing inferences on the message level may have occured immediately. Moreover, by examining the way of cueing (i.e., ambiguous vs. unambiguous cueing) this type of information for communicative intentions appeared to be only effective when the cues were unambiguous by matching pragmatic conventions. The findings suggest that cueing communicative intentions may immediately affect language comprehension, albeit depending on pragmatic conventions of the cues’ usage.